Peran Manajemen Sumber Daya Insani: Kajian di Baznas Ponorogo - Saputro, Ani Dwi; Rois, Adib Khusnul (Universitas Islam Negeri Raden Intan Lampung, 2017)
This study examines the management pattern and Human Resource utilization in Baznaz Ponorogo. The goal is to find out how far the principles of HR management are implemented in the agency. The result of the study shows that the pattern of management and human resources utilization in Baznas Ponorogo covers all aspects, from the recruitment process, placement, until the evaluation of employee performance. In every stage of the process, Baznas Ponorogo not only relies on the principle of professionalism but also considers personal integrity and spiritual maturity aspects. Such is done based on the consideration that a job, if done professionally and sincerely, will yield ina higher value and quality.